Déontologie et minimalisme - Eirick Prairat (Recherches en Éducation)
This paper offers some thoughts concerning a professional code of ethics in teaching. More specifically, it will defend the view that a form of deontology has become desirable. The impulse behind this deontological argument is not some moral aspiration. Rather it is a clear-sighted response to the changes that have occurred in society ant within the more specific domain of teaching practices. This paper will primarily seek to define the idea of deontological minimalism by means of a tripartite characterization, and will demonstrate that it is likely to be the only form of regulation that is compatible with the pluralism of contemporary professions.